Eco-Inclined Fashion Products; Expressing The Green Quality Through Design Lines - Saliang, Prinses; Ujang, Baharuddin; P. Toyong, Natrina Marianne (2016)

(untitled)
The purpose of this study was to express the message of eco-fashion through design principles form follows function; by fully utilizing materials, avoiding fabric waste and enhancing collection of clothing using eco-design principles. The final product circulated within the exploration of basic shapes that had eventually lead to a solid form of a fashion product. The product was built according to design criteria that consist of usability, aesthetic and technical input. These criteria are formulated according to the findings of the three research questions in relation to global warming and fashion industry’s issue. The literature review indicated the importance of new approaches in eco fashion. Collaboratively, modular system, durability and efficiency are the qualities identified in product design that may be implemented in fashion product. This active self-experiential practical process exercised critical thinking, problem solving, using technology and minor engineering in fashion product. Data were collected in two phases; firstly in justifying the issue and secondly, collecting contextual and visual evidences in relation to the research questions. Methods for collecting data included ethnographic, market research, visualization and user testing. The findings from this study included four main designs that features more than one function for each design, which proved that modular system efficient design and durable material were relevant in the study. The essence of designing in this project is using simple shapes that lead to sophisticated form